PENGARUH LOCUS OF CONTROL DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA - Muchammad Rully Sjahirul Alim (Value Added : Majalah Ekonomi dan Bisnis, 2021)
This research was motivated by the influence of globalization, where it hasan impact on human life as expressed by R. Robertson (2011) that globalization isa process of diminishing the individual and the growing awareness of theindividual.This study uses independent variables, locus of control (X1), karaakteristikindividuals (X2), and the performance of the employee as the dependent variable(Y). Research  using questionnaires distributed to 62 people on the administrativestaff of University of Muhammadiyah Semarang by using purposive sampling.While the analysis is done by using SPSS version 16.0 for Windows.Regression analysis and t-test can be seen that the locus of control variable,the variable characteristics of the individual, and the Islamic work ethic variablepositive effect on employee performance variables. The coefficient of determinationR2 of variables Islamic work ethic was 81.8%. This means that the moderatingvariables were able to explain 81.8% while the variations and other variations inthe amount of 100% - 81.8% = 18.2% is explained by other variables that are notaddressed in this study.